2018
DOI: 10.1101/263954
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Age-dependent dormant resident progenitors are stimulated by injury to regenerate Purkinje neurons

Abstract: 25Outside of the neurogenic niches of the brain, postmitotic neurons have not been 26 found to undergo efficient regeneration. Here we demonstrate that Purkinje cells 27 (PCs), which are born at midgestation and are crucial for both development and 28 function of cerebellar circuits, are rapidly and fully regenerated following their 29 ablation at birth. New PCs are produced by a previously unidentified progenitor 30 population and support normal cerebellum development. The number of PC 31 progenitors and thei… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Since upregulation of Ascl1 peaks 3-4 days after injury, the critical events required to produce the Ascl1 + transitory cell state must occur befor P5. Interestingly, in another study we showed that upon depletion of Purkinje cells in the newborn CB, although new Purkinje cells are generated, BgL-NEPs do not undergo adaptive reprogramming to produce them (Bayin et al, 2018). Thus, the type of injury/cell type killed is instrumental in determining the downstream regenerative response of NEPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since upregulation of Ascl1 peaks 3-4 days after injury, the critical events required to produce the Ascl1 + transitory cell state must occur befor P5. Interestingly, in another study we showed that upon depletion of Purkinje cells in the newborn CB, although new Purkinje cells are generated, BgL-NEPs do not undergo adaptive reprogramming to produce them (Bayin et al, 2018). Thus, the type of injury/cell type killed is instrumental in determining the downstream regenerative response of NEPs.…”
Section: Discussionmentioning
confidence: 99%
“…The late development of the CB leads to increased susceptibility to injury around birth and cerebellar hypoplasia is the second leading risk factor of autism spectrum disorders (Wang et al, 2014). Interestingly, the newborn rodent CB can efficiently replenish at least two of its main cell types when they are ablated (Altman and Anderson, 1971; Altman et al, 1969; Bayin et al, 2018; Wojcinski et al, 2017; Wojcinski et al, 2018), and one repair process involves unexpected progenitor plasticity and a glial to neural fate switch after injury. The molecular mechanisms that drive progenitor plasticity in vivo however are unknown in the neonatal CB.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, preterm birth has been linked to 60 cerebellar hypoplasia and multiple neurological dysfunctions (Allen, 2008 the EGL is rapidly reconstituted several days after depletion by irradiation 76 (Altman et al, 1969), we found that the CB of neonatal mice is capable of 77 substantial recovery and production of an adult CB with 70-80% of the normal 78 size and normal morphology after significant ablation of GCPs in the EGL by 79 irradiation at postnatal day (P) 1 (Wojcinski et al, 2017). Furthermore, PCs are 80 completely replenished when ~50% are killed at P1, in an age-dependent 81 process that involves a rare immature PC population proliferating and producing 82 new PCs (Bayin et al, 2018). Thus, at least two cell types in the CB are 83 effectively replenished when ablated soon after birth, and each involves a distinct 84 cellular process.…”
Section: Introduction 51mentioning
confidence: 99%